2016
DOI: 10.3389/fnsys.2016.00021
|View full text |Cite
|
Sign up to set email alerts
|

Compression of Space for Low Visibility Probes

Abstract: Stimuli briefly flashed just before a saccade are perceived closer to the saccade target, a phenomenon known as perisaccadic compression of space (Ross et al., 1997). More recently, we have demonstrated that brief probes are attracted towards a visual reference when followed by a mask, even in the absence of saccades (Zimmermann et al., 2014a). Here, we ask whether spatial compression depends on the transient disruptions of the visual input stream caused by either a mask or a saccade. Both of these degrade the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…These examples stress the power of other visual objects to bias the perceived location of masked stimuli. Previously, we have found strong attraction of a masked probe towards a stable reference (Born et al., 2016; Zimmermann et al., 2014); that is, the opposite of the current bias. However, the probe was only briefly flashed (<50 ms).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…These examples stress the power of other visual objects to bias the perceived location of masked stimuli. Previously, we have found strong attraction of a masked probe towards a stable reference (Born et al., 2016; Zimmermann et al., 2014); that is, the opposite of the current bias. However, the probe was only briefly flashed (<50 ms).…”
Section: Discussionmentioning
confidence: 92%
“…In the first experiment (Experiment 1a), observers judged the distance between alternating bars, comparing a condition with a luminance noise pattern presented during the off-phase of the stimuli to a condition without luminance noise. Based on our previous findings (Born et al., 2016; Zimmermann et al., 2014), my initial hypothesis was that masking of apparent motion results in underestimations of the spacing between bars in the condition with noise. Surprisingly, however, observers judged the spacing between bars as wider with noise (Figure 2(a)).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mislocalization of flashed stimuli can also occur during fixation. Some studies have reported that a briefly flashed stimulus followed by a mask is mislocalized toward a visual anchor in a pattern similar to saccadic compression (Zimmermann, Born, et al, 2014;Born, Krüger, Zimmermann, & Cavanagh, 2016). To test whether we could reproduce this effect, and whether it would also produce mislocalization toward the fixation point, we measured localization after backwards masking, closely following the experimental protocol of Zimmermann, Born, et al (2014).…”
Section: Experiments 3: Masked At Fixationmentioning
confidence: 99%